Synthesis and Biological Evaluation of New CRH Analogues - Spyridon Papazacharias; Vassiliki Magafa; Nicole Bernad; George Pairas; Georgios A. Spyroulias; Jean Martinez; Paul Cordopatis (Bioinorganic Chemistry and Applications)
A series of 7 new human/rat Corticotropin Releasing Hormone (h/r-CRH) analogues were synthesized. The induced alterations include substitution of Phe at position 12 with D-Phe, Leu at positions 14 and 15 with Aib and Met at positions 21 and 38 with Cys(Et) and Cys(Pr). The analogues were tested regarding their binding affinity to the CRH-1 receptor and their activity which is represented by means of percentage of maximum response in comparison to the native molecule. The results indicated that the introduction of Aib, or Cys derivatives although altering the secondary structure of the molecule, did not hinder receptor recognition and binding.